2011
DOI: 10.3113/fai.2011.0457
|View full text |Cite
|
Sign up to set email alerts
|

Ligament Balancing for Total Ankle Arthroplasty: An in vitro Evaluation of the Elongation of the Hind- and Midfoot Ligaments

Abstract: Components of the deltoid ligament complex elongated largest at the ankle joint with any hindfoot movement but inversion. Therefore, selective release of components of the deltoid ligament complex may provide a means for achieving optimal ligament balancing in total ankle arthroplasty. Specifically, release of the superficial and deep posterior tibiotalar ligament may improve range of motion in total ankle arthroplasties, whereas the release of the tibiocalcaneal ligament may correct a varus talar tilt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…are dependent on preoperative planning, operative technique, and anatomic balancing. 12,22 Currently, contraindications for a TAR include 1,2,4 a history of infection, neuromuscular dysfunction, Charcot arthropathy, severe osteopenia, and osteonecrosis of the talus. Relative contraindications include a prior arthrodesis and diabetes.…”
mentioning
confidence: 99%
“…are dependent on preoperative planning, operative technique, and anatomic balancing. 12,22 Currently, contraindications for a TAR include 1,2,4 a history of infection, neuromuscular dysfunction, Charcot arthropathy, severe osteopenia, and osteonecrosis of the talus. Relative contraindications include a prior arthrodesis and diabetes.…”
mentioning
confidence: 99%
“…A recent study by Miller et al demonstrated the presence a rich anastomotic network of arterial supply to the talus both intraosseously and extraosseously. 24 A reduction in blood supply to the talus by disrupting arterial branches over a certain threshold may increase the risk of AVN similar to the phenomenon observed in a displaced talar neck fracture. 4,7,10,15,21,23 AVN of the talus is a rare but recognized complication after a triple arthrodesis.…”
Section: Discussionmentioning
confidence: 92%
“…Direct release of the superficial deltoid ligament for the varus ankle during replacement surgery has been advocated by many. 7,12 This can be easily done by sweeping the fibers of the superficial deltoid ligament off the medial malleolus superiorly with an elevator. The release is done carefully until the medial joint space opens up and the ankle is balanced.…”
Section: Extra-articular Varus Ankle Deformitymentioning
confidence: 99%
“…Recently, Merian et al 12 published results on a cadaveric study that evaluated the elongation of ligaments about the hindfoot in response to alterations in ankle orientation. They found that components of the deltoid ligament complex elongated the most at the ankle joint with any hindfoot movement but inversion.…”
Section: Extra-articular Varus Ankle Deformitymentioning
confidence: 99%
See 1 more Smart Citation